1972
DOI: 10.1063/1.1677978
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Molecule Reactions in Silane

Abstract: The reactions of primary ions Si+, SiH+, SiH2+, and SiH3+ with SiH4 are observed and reported, along with relative and absolute rate constants for the reactions observed. SiH2+ and SiH3+ are seen to undergo H− transfer reactions with large rate constants. All of the ions also participate in reactions yielding higher molecular weight ions containing two silicon atoms. The rate constants for many of these reactions are also large and suggest that the production of higher silanes from silane in activated systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…All reactions of SiH; with H2 are endothermic [64]. [188] (multiplied by a factor 1.15 to account for the new value of the methane proton transfer rate eonstant a s suggested in [187]); e: RBENTS et al [189]; f: MANDICH and F~EENTS [190]; g: R E E N T S '~~~ MANDICH [191]; h: MANDICH et al [68]; i: MANDICH and REENTS [78]: j: F~EENTS and MANDICH [192], summary of their work and of the total rate constants.…”
Section: A T I O N -M O L E C U L E R E a C T I O N S Si H Y D R I mentioning
confidence: 99%
“…All reactions of SiH; with H2 are endothermic [64]. [188] (multiplied by a factor 1.15 to account for the new value of the methane proton transfer rate eonstant a s suggested in [187]); e: RBENTS et al [189]; f: MANDICH and F~EENTS [190]; g: R E E N T S '~~~ MANDICH [191]; h: MANDICH et al [68]; i: MANDICH and REENTS [78]: j: F~EENTS and MANDICH [192], summary of their work and of the total rate constants.…”
Section: A T I O N -M O L E C U L E R E a C T I O N S Si H Y D R I mentioning
confidence: 99%
“…The most elementary system involved in this area of study is that of monosilane. Monosilane has been investigated by Gaspar et al [37] and Lampe et al [38] and it has been shown that all the primary ions of SiH 4, namely, Si +, SiH +, SiH~, andL SiH~, react with SiH 4. The relatively small amount [39], indeed if any, of SiH~ is due to the inherent instability of the ion.…”
Section: Reactionsmentioning
confidence: 99%
“…It should be mentioned that comparison of the rate of depletion of SiH~ to the rate of formation of SiH~ in Figure 6 illustrates that SiH~ does not undergo hydride ion transfer exclusively. ICR studies [37] and tandem mass spectrometry [38] confirm (111-4) as another reaction of SiH~ with SiH 4 . Although single-source pressure dependence studies establish (111-2) as the major exothermic reaction for SiH + with SiH 4, they do not account for the total 0.7 Figure 6.…”
Section: Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29] Nanoparticle morphologies can greatly differ at different stages of the growth, especially in their crystal structures. As a result of the exothermic nature of the growth reactions [30][31][32] that take place during nucleation, nanoparticles have monocrystalline, defect-free morphology. On the other hand, during post-nucleation stage, depending on the temperature, nanoparticles coagulate ending up with polycrystalline morphology, which contains defects and discontinuities due to the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%